Outcomes of Coronavirus Disease 2019 (COVID-19) Related Hospitalization Among People With Human Immunodeficiency Virus (HIV) in the ISARIC World Health Organization (WHO) Clinical Characterization Protocol (UK): A Prospective Observational Study. (23rd October 2020) - Geretti, Anna Maria; Stockdale, Alexander J; Kelly, Sophie H; Cevik, Muge; Collins, Simon; Waters, Laura; Villa, Giovanni; Docherty, Annemarie; Harrison, Ewen M; Turtle, Lance; Openshaw, Peter J M; Baillie, J Kenneth; et al.
Abstract: Background: Evidence is conflicting about how human immunodeficiency virus (HIV) modulates coronavirus disease 2019 (COVID-19). We compared the presentation characteristics and outcomes of adults with and without HIV who were hospitalized with COVID-19 at 207 centers across the United Kingdom and whose data were prospectively captured by the International Severe Acute Respiratory and Emerging Infection Consortium (ISARIC) World Health Organization (WHO) Clinical Characterization Protocol (CCP) study. Methods: We used Kaplan-Meier methods and Cox regression to describe the association between HIV status and day-28 mortality, after separate adjustment for sex, ethnicity, age, hospital acquisition of COVID-19 (definite hospital acquisition excluded), presentation date, 10 individual comorbidities, and disease severity at presentation (as defined by hypoxia or oxygen therapy). Results: Among 47 592 patients, 122 (0.26%) had confirmed HIV infection, and 112/122 (91.8%) had a record of antiretroviral therapy. At presentation, HIV-positive people were younger (median 56 vs 74 years; P  < .001) and had fewer comorbidities, more systemic symptoms and higher lymphocyte counts and C-reactive protein levels. The cumulative day-28 mortality was similar in the HIV-positive versus HIV-negative groups (26.7% vs. 32.1%; P  = .16), but in those under 60 years of age HIV-positive status was associated with increased mortality (21.3% vs. 9.6%; P  < .001 [log-rank test]). Mortality was higher among people with HIV after adjusting for age (adjusted hazard ratio [aHR] 1.47, 95% confidence interval [CI] 1.01–2.14; P  = .05), and the association persisted after adjusting for the other variables (aHR 1.69; 95% CI 1.15–2.48; P  = .008) and when restricting the analysis to people aged <60 years (aHR 2.87; 95% CI 1.70–4.84; P  < .001). Conclusions: HIV-positive status was associated with an increased risk of day-28 mortality among patients hospitalized for COVID-19. Abstract : People with human immunodeficiency virus (HIV) hospitalized with coronavirus disease 2019 (COVID-19) had an age-adjusted 47% higher risk of day-28 mortality compared with a large population of HIV-negative people within the same data set. The effect persisted after adjusting for sex, ethnicity, and major comorbidities.